Detection of Quadruplex DNA by Gold Nanoparticles - Heather F. Crouse; Alex Doudt; Cassie Zerbe; Swarna Basu (Journal of Analytical Methods in Chemistry)
Gold nanoparticles have been used as a probe to detect low (<10 ppb) concentrations of quadruplex DNA. These nanoparticles display a tendency to form aggregates in the presence of certain quadruplex forms, as observed via enhanced plasmon resonance light scattering (PRLS) signals. These nanoparticles showed differing degrees of interactions with different types of quadruplex and mixed sequences but no interaction with duplex DNA. Enhancement of PRLS signals greater than 50% was observed at nanomolar DNA concentration, and a lower limit of detection of 2.1 nM was established for three different quadruplex DNA sequences, including the thrombin-inhibiting single-stranded 15 mer aptamer DNA, d(GGTTGGTGTGGTTGG), and the double-stranded 12 mer DNA, d(G4T4G4). Two different sample preparation protocols were used for the PRLS experiments, and they yielded similar results.